2022
DOI: 10.1021/acs.est.2c05888
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 18 Organophosphate Esters and 3 Organophosphite Antioxidants in Food Contact Materials Using Suspect and Nontarget Screening: Implications for Human Exposure

Abstract: In this study of extracts of 100 food contact material (FCM) samples collected from South China, we identified 21 organophosphate esters (OPEs) by suspect screening and seven novel OPEs by characteristic fragments-based nontarget screening. Six organophosphite antioxidants (OPAs) were further identified using a suspect list derived from these identified OPEs. Of these compounds, 18 OPEs and 3 OPAs were found for the first time in the extracts of FCMs. (Semi-)quantification revealed that seven of the OPEs [trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 36 publications
1
36
1
Order By: Relevance
“…However, over the past 5 years, AO168�O has been frequently detected in the environment, typically at higher levels than target OPEs. 70,72,73 In this study, AO168�O (Figure S12) was found in all soil and blank samples, and thus the concentration was not reported. Nevertheless, two other metabolites of AO168, namely, the hydroxylation product AO168_M1 (Figure S13) and the methylation product AO168_M2 (Figure S14), were identified as level 2.…”
Section: Agricultural Soilmentioning
confidence: 66%
See 2 more Smart Citations
“…However, over the past 5 years, AO168�O has been frequently detected in the environment, typically at higher levels than target OPEs. 70,72,73 In this study, AO168�O (Figure S12) was found in all soil and blank samples, and thus the concentration was not reported. Nevertheless, two other metabolites of AO168, namely, the hydroxylation product AO168_M1 (Figure S13) and the methylation product AO168_M2 (Figure S14), were identified as level 2.…”
Section: Agricultural Soilmentioning
confidence: 66%
“…AO168 is a typical organophosphite antioxidant additive mainly used to protect plastic polymer materials from hydroperoxides and can thus be readily released. AO168 was detected in high concentrations in commercial polymer products, such as disposable masks (mean: 111 ng/g), mulch film (median: 3480 ng/g), and food packaging (median: 3190 ng/g) . Additionally, AO168 has been identified in environmental matrices, such as soil, air particles, and indoor dust, , but has never been detected in environmental waters except for one instance in bottled mineral water .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OPAs are susceptible to being oxidated to OPAs = O (the oxidation derivatives of OPAs) accounting for a pair of unbonded electrons of the trivalent phosphorus atom . Although they are reported at much lower levels than for OPAs = O, their contribution to OPAs = O in the environment cannot be neglected, especially for tris (2,4-di- tert -butylphenyl)­phosphite (TDtBPPi, also named AO168) and its oxidation derivative tris (2,4-di- tert -butylphenyl)­phosphate (AO168 = O). For instance, our previous study has demonstrated that AO168 = O was the primary OPA = O contaminant in farmland soil attributed to the release from mulch films …”
Section: Introductionmentioning
confidence: 99%
“…Dietary intake of OPAs and OPEs is an essential human exposure pathway with an exposure dose comparable to or higher than air inhalation and dust ingestion. , They have been frequently detected in drinking water and foodstuffs worldwide. ,, However, the exposure of OPAs and their oxidative products (OPAs = O) was rarely included. Recently, Wang et al, identified 18 OPEs and 3 OPAs in food packaging materials by suspect and nontarget screening, in which AO168 and AO168 = O were the dominant pollutants with median concentrations of 7260 and 31920 ng/g, respectively. This indicates a high dietary exposure risk for exposure to OPAs and OPEs in humans.…”
Section: Introductionmentioning
confidence: 99%